Planning Of Facilities And Infrastructure In Annur Darunnajah 8 Boarding Schools In Cidokom Gunung Sindur In Improving Teachers Religious Competence - Yulianto, Tri; Endin Mujahidin, Endin; Hasbi Indra, Hasbi; Abdul Hayyie Al-Kattani , Abdul; Nesia Andriana, Nesia (Mudir : Jurnal Manajemen Pendidikan, 2024)
In an educational institution called a school, it must have a facility and infrastructure management system, so that all activities become effective and efficient. Facilities and infrastructure are one of several systems to improve the quality of students, therefore the management of facilities and infrastructure at Pondok Darunnajah 8 school has a good quality system. This can be seen from the various facilities and participation of students in being responsible for managing school facilities and infrastructure. Thus Pondok Darunnajah 8 is one of the schools that has quality facilities and infrastructure so that it can be a tool or material in improving all the quality of students. The method used is a qualitative descriptive method carried out at the Annur Darunnajah Islamic Boarding School 8 Gunung Sindur Bogor. With data collection techniques in the form of observation, interviews, and documentation. Sources of informants included school principals, school facilities and infrastructure, teachers, school heads and students. The results of the research show that: (1) Pondok Darunnajah 8 has a clear sectional structure and is engaged in their respective fields. (2) Management of facilities and infrastructure is carried out collaboratively by all components of the school, so that the management is carried out properly starting from procurement, inventory storage, arrangement, main person in charge and maintenance. (3) Types of facilities and infrastructure can be viewed from their function, type and nature. (4) The scope of facilities and infrastructure is divided into four: planning of facilities and infrastructure, procurement of facilities and infrastructure, use of facilities and infrastructure, and elimination of facilities and infrastructure. (5) Maintenance of facilities and infrastructure at Pondok Darunnajah 8 is carried out daily or every other day and periodically.